Students’ mathematical reasoning ability on system of linear equation in two variables using video media, PMRI, and collaborative learning - Sugiharto, Mugi Arif; Putri, Ratu Ilma Indra (AIP conference proceedings, 2023)
Mathematical reasoning ability is a fundamental ability which students need because it helps students understand the abstract mathematical concepts. However, there are still students with low mathematical reasoning abilities, especially in the system of linear equation in two variables (SLETV) topic. This research is a descriptive study to determine the eight-grade students’ mathematical reasoning abilities on the SLETV material after joining a learning using video media, Indonesian RME (PMRI) approach, and collaborative learning. The research subjects were students of class VIII.6 of SMP Negeri 1 Palembang, a group of eight-grade students in a public junior high school in Palembang, Indonesia. We focused on three students with high, medium, and low academic abilities. We collected the data through observation, written test with two questions, and interviews. The data were then analyzed qualitatively by data reduction, presentation, and conclusion. The results showed that the high frequently emerging indicators of mathematical reasoning ability were presenting mathematical statements, mathematical manipulation, and concluding, meanwhile the rarely emerging indicators were making conjectures and checking the validity of arguments.